Expression and role of microRNA-1271 in the pathogenesis of osteosarcoma - Lu, Gongbiao (Exp Ther Med, 2018)
The aim of the current study was to investigate the expression and role of microRNA (miR)-1271 in the pathogenesis of osteosarcoma, and the associated underlying mechanisms. Tissue samples from 45 patients with osteosarcoma were collected, while the 143B, MG-63 and U-2 OS osteosarcoma cell lines were also cultured. The expression levels of miR-1271 in the tissues and cells were detected with reverse transcription-quantitative polymerase chain reaction, and 143B osteosarcoma cells were subjected to miR-1271 manipulation. In addition, the cell proliferation, cell cycle progression, and migration and invasion abilities were assessed by Cell Counting Kit-8 assay, flow cytometry and Transwell chamber assay, respectively. Tissue inhibitor of metalloproteinases 2 (TIMP2) expression level was also detected with western blot analysis. Dual-luciferase reporter assay was performed to investigate the interaction between miR-1271 and TIMP2. The results revealed that miR-1271 expression was significantly elevated in the osteosarcoma tissue and was closely correlated with the clinical TNM staging. The expression levels of miR-1271 were also upregulated in the osteosarcoma cells, with the highest expression observed in 143B cells. Inhibition of miR-1271 significantly inhibited the cell proliferation, G1/S phase transition, and the migration and invasion abilities of 143B cells, while it also resulted in upregulated TIMP2 expression in these cells. Furthermore, overexpression of TIMP2 significantly inhibited the cell proliferation, G1/S phase transition, and migration and invasion abilities of 143B cells. Dual-luciferase reporter assay demonstrated that miR-1271 targeted on the 3′-untranslated region of TIMP2 mRNA. In conclusion, the expression levels of miR-1271 were significantly elevated in osteosarcoma tissues and cells. miR-1271 downregulated the expression of TIMP2 to promote the proliferation and enhance the migration and invasion abilities of 143B osteosarcoma cells, functioning as an oncogene.